FORMULASI DAN UJI EFEKTIVITAS SEDIAAN GEL KOMBINASI DARI EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus) DAN DAUN PEPAYA (Carica papaya L) TERHADAP PENYEMBUHAN LUKA BAKAR TIKUS PUTIH JANTAN (Rattus norvegicus) - SEMBIRING, TIO RANTI SARI (Jurnal Penelitian Farmasi Dan Herbal, 2024)
ABSTRACK Background: According to research conducted at Cipto Mangunkusumo Hospital (RSCM) in 2011-2012, it was reported that the average age was 28 years from a range of 2.5 months to 76 years, while the mortality rate was 36.6% in patients with extensive burns. more than 60.0% of them all experienced death. Research was carried out at the Pharmaceutical Biology Laboratory and the Pharmaceutical Qualitative Laboratory at the Deli Husada Deli Tua Health Institute, as well as at the Pharmaceutical Preparation Technology Laboratory for the manufacture of extracts and gel preparations. The research took place from March to May 2024. This research is a laboratory experimental research. The research population is jackfruit leaves and papaya leaves. The samples used were jackfruit leaf and papaya leaf extracts with concentrations of 3%, 6%, 9%, as well as bioplacenton gel. Research procedures include making simplicia, making extracts using the maceration method, characterization of simplicia, as well as formulation and quality eval_uation of gel preparations. Effectiveness testing was carried out by observing the healing time of burn wounds in mice treated with ethanol extract gel from jackfruit leaves and papaya leaves. The results of this study showed that the effectiveness of healing burn wounds from the combination of ethanol extracts from jackfruit leaves and papaya leaves every day in each formulation. In the positive control (bioplasma) at a concentration of 6% there was no significant difference of p0.05 on days 3, 6, 12 and 15. On day 9 there was a significant difference of p0.05 in each formulation. However, it can be concluded that the 6% concentration is the most effective in healing burns. The bioplacenton gel preparation has better effectiveness in healing wounds compared to the gel preparation combining the ethanol extract of jackfruit leaves and papaya leaves. Keywords: Artocarpus heterophyllu,Carica papaya L, effectiveness test